The cost-efficacy of a healthy food box for managing hypertension within a native American population: a group randomized controlled trial - Austin Henderson; Robert Rosenman; Amber L. Fyfe-Johnson; Tori Taniguchi; Joy Standridge; Tyra Shackleford; Clemma J. Muller; Jason G Umans; Valarie Blue Bird Jernigan (BMC, 2024)
Abstract Background Dietary interventions are used for the treatment of hypertension. We evaluated the cost-efficacy of delivering boxes of healthy, culturally tailored foods and checks that can only be spent on produce in a Native American population. Methods We conducted a group randomized controlled trial from 2018 to 2020 with N = 2 treatment counties and N = 2 control counties and a total of N = 160 Native American adults with baseline stage 1 or stage 2 hypertension. Participants in the intervention group received monthly boxes of food that adheres to the Dietary Approaches to Stop Hypertension diet as well as checks that could only be spent on produce for 6 months. We measured blood pressure and quality of life at baseline and at a 6-month follow-up in both intervention and control groups. We used ordered logistic regression to estimate the effect of treatment on probability of blood pressure improvements. We then conducted a cost-efficacy analysis. Results We found that treatment was effective in reducing blood pressure in women with stage 1 hypertension at baseline. Based on this finding, we also estimate that this intervention satisfies normative cost-effectiveness thresholds, even when lifetime treatment is needed to preserve the impact, so long as treatment is only continued in those who respond to treatment. Conclusions Direct delivery of healthy foods and checks that can only be spent on produce are a potentially cost-effective intervention for the management of hypertension among Native American women with stage 1 hypertension. Further research is needed to understand why we found an impact only for this group.